2011
DOI: 10.1093/neuonc/nor035
|View full text |Cite
|
Sign up to set email alerts
|

Control of proliferation in astrocytoma cells by the receptor tyrosine kinase/PI3K/AKT signaling axis and the use of PI-103 and TCN as potential anti-astrocytoma therapies

Abstract: A growing body of work suggests that astrocytomas and glioblastoma multiforme will require carefully tailored, molecularly targeted therapy for successful treatment. Recent efforts to comprehensively identify mutations and gene expression changes in glioblastoma have shown that mutation of NF1 is a common alteration in human glioblastoma. We have developed and characterized a panel of 14 tumor lines from grades II through IV astrocytomas developed from our Nf1-/+;Trp53-/+cis mouse model and have used this pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…In addition, TCN downregulated p-AKT, HIF-1α and VEGF in ESCC cells, and suppressed the growth of ESCC xenografts. These results may complement those from previous studies on TCN, which suggested that TCN may be an antitumor agent in different cancers, and may expand our understanding of the mechanisms of TCN activity (18).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, TCN downregulated p-AKT, HIF-1α and VEGF in ESCC cells, and suppressed the growth of ESCC xenografts. These results may complement those from previous studies on TCN, which suggested that TCN may be an antitumor agent in different cancers, and may expand our understanding of the mechanisms of TCN activity (18).…”
Section: Discussionsupporting
confidence: 81%
“…HIF-1α is an oxygen-sensitive subunit (14), which, under hypoxic conditions, is an important factor for tumor cells to resist IR (15). TCN, which was initially described as a DNA synthesis inhibitor, has recently been shown to function as an inhibitor of AKT (18). Previous studies demonstrated that TCN inhibits AKT phosphorylation at Thr308 and Ser473 and AKT activity in the human prostate cancer cell line PC-3 (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have demonstrated that EGFR is overexpressed in 60-90% of glioblastomas (36), as well as in C6 glioma cells (25). hyperactivated EGFR signaling promotes cell growth and inhibits apoptosis via its major downstream and crosstalk signaling pathways, such as PI3K/AKT/mTOR and RAS/MAPK, which can regulate cell survival, proliferation, invasion and angiogenesis (37)(38)(39). Our previous studies have demonstrated that antisense and dominantnegative EGFR cDNA or siRNA targeting EGFR effectively inhibit glioma cell growth (25,40).…”
Section: Discussionmentioning
confidence: 99%